The role of development cooperation for upgrading in Uganda's organic fruit value chain - Michael Vysin (Südwind-Verlag, 2017)
In his master's thesis, Michael Vysin examines the role of development cooperation for upgrading processes in the organic fruit sector in Uganda. He takes the example of mangoes and pineapples which are the main export products in this sector in Uganda and focuses on the perspective of export companies. As a theoretical framework, he uses the global value chain approach and particularly the upgrading concept and links it to the concept of private sector development in international development cooperation. He presents different dimensions of the value chain approach, describes forms of upgrading, and also discusses the limits of this approach. Subsequently, he examines the role and importance of private sector development in international development cooperation. In the empirical part, Vysin first gives an overview of the economic situation of Uganda in general and the agricultural and organic fruit sector in particular. For his empirical research, Vysin conducted interviews with actors in the organic fruit sector in Uganda. His research shows that interventions of development cooperation have significantly supported upgrading processes, above all in the field of processing. As a consequence, exporters were enabled to produce and export dried fruits - instead of fresh fruits - which increased value addition of their activities. Donor interventions focused mainly on equipment, recruitment of farmers, training, business linkages and certification. In addition to a focus on the company level, sector-specific institutions were supported, which proved to be central to the broader effectiveness and sustainability of the interventions. Nevertheless, Vysin also identifies challenges that need to be addressed to ensure the sustainability of donor interventions. These consist, inter alia, in access to affordable loans for further investments by exporters, in the improvement of production conditions for farmers as well as in the establishment or consolidation of local institutions. In his thesis, Vysin succeeded in linking the global value chain approach with the concept of private sector development and applying it to a concrete sector and country example. He was also able to reflect the views of exporters in a broader context, as well as to develop recommendations, which makes his thesis an interesting lecture not only for scholars but also for development practitioners.
Keywords: 330